Traffic modeling and performance evaluation of SDN‐based NB‐IoT access network. (4th February 2019) - Chen, Xin; Li, Zhuo; Chen, Ying; Du, Bing; Zhang, Yongchao
Summary: Narrow Band Internet of Things (NB‐IoT) is a cellular‐based low power wide area network (LPWAN) radio technology, which can provide highly reliable services and wide coverage for IoT devices. Software defined networking (SDN) as an emerging network architecture can realize flexible resource allocation and network management. We introduce SDN into NB‐IoT and investigate the traffic modeling and performance evaluation of SDN‐based NB‐IoT access network. To evaluate the network performance in different environments, we introduce the Beta/D/1, Uniform/D/1, and M/D/1 queuing models, respectively. The proposed queuing models are suitable for different scenarios, in which NB‐IoT devices access the network in a highly synchronized, unsynchronized, or stochastic manner. We use the general solution to the G/G/1 and the M/G/1 queuing model to solve the proposed modeling problems. Through simulations, we investigate the influence of different network parameters. The analysis and simulation results can be used in the SDN controller to dynamically allocate resources and make network management decisions to satisfy different performance requirements of NB‐IoT applications.